Predictors of sickness absence and intention to leave the profession among NHS staff in England during the COVID-19 pandemic: a prospective cohort study - Neil Greenberg; Rosalind Raine; Paul Moran; Dominic Murphy; Lauren J Scott; Richard Morriss; Sharon A M Stevelink; Simon Wessely; Ira Madan; Chris Penfold; Sarah Dorrington; Anne Marie Rafferty; et al. (BMJ Open)
Objectives This study aims to determine key workforce variables (demographic, health and occupational) that predicted National Health Service (NHS) staff’s absence due to illness and expressed intention to leave their current profession.Design, setting and participants Staff from 18 NHS Trusts were surveyed between April 2020 and January 2021, and again approximately 12 months later.Outcome measures Logistic and linear regression were used to explore relationships between baseline exposures and four 12-month outcomes: absence due to COVID-19, absence due to non-COVID-19 illness, actively seeking employment outside current profession and regularly thinking about leaving current profession.Results 22 555 participants (out of a possible 152 286 employees; 15%) completed the baseline questionnaire. 10 831 participants completed the short follow-up questionnaire at 12 months and 5868 also completed the long questionnaire; these participants were included in the analyses of sickness absence and intention to leave, respectively. 20% of participants took 5+ days of work absence for non-COVID-19 sickness in the 12 months between baseline and 12-month questionnaire; 14% took 5+ days of COVID-19-related sickness absence. At 12 months, 20% agreed or strongly agreed they were actively seeking employment outside their current profession; 24% thought about leaving their profession at least several times per week. Sickness absence (COVID-19 and non-COVID-19 related) and intention to leave the profession (actively seeking another role and thinking about leaving) were all more common among NHS staff who were younger, in a COVID-19 risk group, had a probable mental health disorder, and who did not feel supported by colleagues and managers.Conclusions Several factors affected both workforce retention and sickness absence. Of particular interest are the impact of colleague and manager support because they are modifiable. The NHS workforce is likely to benefit from training managers to speak with and support staff, especially those experiencing mental health difficulties. Further, staff should be given sufficient opportunities to form and foster social connections. Selection bias may have affected the presented results.